Chronic Psychological Stress, but Not Chronic Pain Stress, Influences Sexual Motivation and Induces Testicular Autophagy in Male Rats - Shen, Yunyun; He, Danni; He, Luhong; Bai, Yu; Wang, Bo; Xue, Yan; Hou, Gonglin (Frontiers in Psychology, 2020)
Spermiogenesis is an important physiological process of mammalian fertilization. The germ cells are susceptible to the harmful effects of either psychological or physiological stress, which could induce male infertility. Our previous studies have found that chronic psychological stress could decrease sexual motivation. However, molecular mechanisms underlying male reproductive toxicity induced by chronic stress remain elusive. Recently, autophagy is proven to be involved in regulating the survival of germ cells, which is related to apoptosis. Herein, we established a chronic psychological stress model and a chronic pain model (physiological stressor) to explore the roles of autophagy in germ cells. Thirty-two male Sprague-Dawley rats were randomly divided into four groups, including the control group, the chronic psychological stress group, the SNI-sham group, and the chronic pain stress group. After exposure to stress for 35 days, open field test and the unconditioned sexual motivation test were performed. Following the behavioral experiment, autophagy in the rat testis was detected by Western blot and immunohistochemistry. We found both chronic psychological stress and chronic pain stress reduced total travel distance, the frequency of central crossing and increased the sensitivity to mechanical pain. While chronic psychological stress, but not the chronic pain stress declined sexual motivation. Chronic psychological stress prompt the expression of LC3-II with the decreased expression of p62, indicating that chronic psychological stress induced autophagy in rat testis. However, there was no significant difference between the expression of LC3-II and p62 in male rats under chronic pain stress. Therefore, chronic psychological stress and chronic pain stress have common behavior changes, but due to its unpredictability, chronic psychological stress leads to a decline in sexual motivation in male rats and induced the autophagy in testicular tissues.